Advances in the pharmacotherapy of chronic heart failure with preserved ejection fraction: an ideal opportunity for precision medicine. (4th March 2017) - Polsinelli, Vincenzo B.; Shah, Sanjiv J.
ABSTRACT: Introduction : Heart failure with preserved ejection fraction (HFpEF), which comprises approximately 50% of all heart failure patients, is a challenging and complex clinical syndrome that is often thought to lack effective treatments. Areas covered : Despite the common mantra that HFpEF has no effective treatments, closer inspection of HFpEF clinical trials reveals that several of the drugs tested are associated with benefits in exercise capacity and quality of life, and reduction in heart failure hospitalization. Here we review major randomized controlled trials in HFpEF, focusing on renin-angiotensin-aldosterone system antagonists, organic nitrates, digoxin, beta-blockers, and phosphodiesterase-5 inhibitors. In addition, we review several classes of drugs currently in development for HFpEF such as neprilysin inhibitors, inorganic nitrates (nitrites), and soluble guanylate cyclase stimulators. Expert opinion : HFpEF should not be viewed as lacking effective treatments. While there have been no breakthrough clinical trials showing a reduction in mortality, several existing medications are likely to benefit specific subgroups of HFpEF patients. HFpEF is now well known to be a heterogeneous syndrome; thus, the clinical management of HFpEF patients and future HFpEF clinical trials will both likely require a nuanced, phenotype-specific approach instead of a one-size-fits-all tactic. Drug development for HFpEF therefore represents an exciting opportunity for personalized medicine.